Four synchronous primary malignancies in one patient - Mišánik, M; Grajciar, M; Daňová, I; Musová, D; Miklušica, J; Tobiášová, K; Smolár, M (Rozhledy v chirurgii, 2025)
Multiple primary malignancy is defined as the occurrence of two or more primary malignancies in one patient. Although this is a rare situation, its occurrence has been increasing over the last decade. Patients with an oncological disease have up to a 20% higher risk of a new primary oncological disease compared to the general population. Depending on the time interval between the diagnosis of individual malignancies, we divide multiple cancer cases into synchronous and metachronous. The diagnosis of four synchronous malignancies is extremely rare. In our case report, we present a patient with caecal adenocarcinoma, hepatic flexure adenocarcinoma, clear cell carcinoma of the right kidney and pheochromocytoma of the right adrenal gland occurring synchronously.
Keywords: pheochromocytoma; nádory nadledvin; Adenocarcinoma, Clear Cell; Carcinoma, Renal Cell; mnohočetné primární nádory; colorectal cancer; multiple primary malignancies; lidé; feochromocytom; adenokarcinom z jasných buněk; adenokarcinom; karcinom z renálních buněk; Cecal Neoplasms; Renal cell carcinoma; Kidney Neoplasms; Neoplasms, Multiple Primary; Humans; quadruple adenocarcinoma; Pheochromocytoma; Adrenal Gland Neoplasms; nádory slepého střeva; Adenocarcinoma; nádory ledvin